PROSPEK ZAKAT DALAM PEREKONOMIAN MODERN (ZISWAF: Jurnal Zakat dan Wakaf, 2014)
Zakat as one means to improve the welfare of the people, increasecommunity resources have excellent prospects in the modern economy.This can be achieved if the charity is managed by the Management ofmodern, using the pattern and strategy of a company. And the needfor cooperation with other Muslim countries both regionally andinternationally.